Identifying the Dominant Factors of Gen Z's Job Satisfaction through the Integration of Empirical Findings: Systematic Literature Review - Syahlidi, Goku; Videlya, Viola; Meliani, Dwi Rosita (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to identify and synthesize the factors that affect Generation Z's job satisfaction through the Systematic Literature Review (SLR) approach. This review analyzes 20 quantitative scientific articles published in the Scopus indexed journal Q1–Q4 quartile in the 2015–2025 range. The study selection process follows the PRISMA guidelines with the support of the Watase Uwake application to ensure transparency and replication of the literature screening procedure. The data obtained were then analyzed using a thematic synthesis approach to group the determinants of job satisfaction into organizational clusters, leadership, job characteristics, and individual psychological factors. The results of the study show that work flexibility is the most consistent determinant in increasing job satisfaction of Generation Z. Other factors that play a significant role include the quality of adaptive leadership, a fair reward system, career development opportunities, meaningful job design, and employee psychological well-being. In contrast, work stress, burnout, and job insecurity have consistently been shown to lower job satisfaction levels. This research makes a theoretical contribution by systematically mapping the determinants of job satisfaction of Generation Z and integrating previously fragmented empirical findings, thereby strengthening the understanding of job satisfaction as a multidimensional construct in the context of the younger generation workforce.